The Five Secrets You Must Discover Before You Die - Izzo, John B. (John Baptist), 1957- (San Francisco, CA : Berrett-Koehler Publishers, Inc., 2008)
John Izzo presents valuable advice that was gleaned from over 200 interviews with people aged 60-106 whom others had said had found the meaning of life. He covers the common themes from the lives of those interviewed, the commonality of what really matters in their lives, and how to put this wisdom into practice.
Why some people find meaning and die happy -- Why I talked to the town barber (and 200 other people over 60) about life -- The first secret : be true to your self -- The second secret : leave no regrets -- The third secret : become love -- The fourth secret : live the moment -- The fifth secret : give more than you take -- When you know you have to go (putting the secrets into practice) -- Preparing to die well : happy people are not afraid to die -- It's never too late to live the secrets.
Includes index.
Formerly CIP.
Keywords: Self-actualization (Psychology); Success